Sosialisasi Metode Geolistrik Untuk Eksplorasi Air Tanah Bagi Siswa SMK Negeri 9 Energi dan Pertambangan Jayapura - Virman; Florentina M. Panda; Paulus G. D. Lasmono; Auldry F. Walukow; Yosfince Inghondem (JURNAL PENGABDIAN PAPUA, 2025)
The purpose of the activity is to provide experience and train participants to understand geoelectric theory, data collection and processing and analysis packaged in the form of reports, and specifically to obtain real input for curriculum development in universities to be more relevant to development needs. Based on the problems experienced by students of SMK Negeri 9 Energy and Mining Jayapura, a service activity was carried out that intends to explain geophysical methods related to groundwater utilization for agriculture. Students will receive material with a ratio of 50% theory and 50% practice. Through this activity, participants will better understand the concepts in searching for groundwater and be able to develop skills, especially in the development of geophysical tools and be able to interpret the measurement results and resistivity values accurately, measurably and integrated. The results of geoelectric data processing of VES 1-3 points show that VES.1 has a relatively larger specific resistance value when compared to the two measurement points VES.2 and VES.3. This difference is due to the structure of VES.1 in the form of hard rock part of the Ultramafic formation which is composed of rock types such as marl, fine sandstone, tuff, and tuff. The results of geoelectric data processing from the four measurement points show that the measurement points VES. 4, VES. 6 and VES. 7 have relatively low specific gravity values, in contrast to the relatively high value of VES. 5 which is relatively high. The difference in specific gravity values is very influential on the presence of aquifers at each measuring point. Based on the distribution of specific gravity values, the vertical lithology of the four measuring points is arranged by rock types, namely surface rocks, breccias, tuffs, clay stones, and siltstones.